Vascular endothelial growth factors and placenta growth factor in retinal vasculopathies: Current research and future perspectives. (February 2018) - Mesquita, Joana; Castro-de-Sousa, João Paulo; Vaz-Pereira, Sara; Neves, Arminda; Passarinha, Luís A.; Tomaz, Cândida T.
Highlights: A review of the function of growth factors VEGF-A, VEGF-B and PlGF in normal development and disease. The implication of VEGF-A, VEGF-B and PlGF in the pathophysiology and pathogenesis of various ophthalmic disorders. The importance of human vitreous and serum VEGF-A, VEGF-B and PIGF in diagnostic and therapy. An analysis of current targeted therapies for retinal diseases. A reflection on new promising molecules in ophthalmology. Abstract: Vision loss due to disease or degeneration of the eye (retina, choroid, retinal veins, or macula) is a leading cause of blindness worldwide. In most cases, vision-threatening ocular diseases are accompanied by abnormal changes in the vasculature of the eye, especially the retina, and these conditions are collectively referred to as retinal vasculopathies. Impaired blood supply or hypoxia stimulates angiogenesis in the vascular and non-vascular sections of the eye, which results in neovascularization, leading to conditions such as diabetic retinopathy or age-related macular degeneration. Studies show that vascular endothelial growth factors: VEGF-A, VEGF-B, and placental growth factor (PlGF) are elevated in these diseases, and hence, these factors could be used as markers for disease prognosis and therapy. In this review, we discuss the function of these growth factors in normal development and disease, with focus on ocular disorders and emphasize the importance of accurately determining their levels in the vitreous and serum of patients for correct diagnosis and therapy.